MEREDUKSI PERILAKU DAN BUDAYA KORUPTIF: UPAYA PEMBENTUKAN KARAKTER ANTI KORUPSI DALAM PERSPEKTIF ETIS TEOLOGI - Soewieto Djajadi (Manna Rafflesia, 2023)
The massive corruption that occurs in this nation also extends to the church as a spiritual institution. Corruption is a big problem for society, which causes people to suffer and, of course, disrupts the country's economy. Corruption is also an act of violation of human rights and is now a social pathology that is dangerous for human life. This research aims to provide an understanding of how the role of Christianity can reduce corrupt behaviour by forming an anti-corruption character. Yeng is certainly very useful for Christianity in building a country free from corruption. This paper uses a descriptive qualitative method with a literature study approach. The results of this research state that corruption is a crime that must be fought. Corruption contains untruths that are not in line with the teachings of the Bible. Therefore, the church must guide the congregation with an anti-corruption character within a biblical framework.